Analisis Pengendalian Kualitas Produk Handle Fr Mnl Seat No.1 (FRONT)/Handle Seat Track (YHA) Dengan Metode Six Sigma di PT. Chiyoda Industri Indonesia - Salsabila, Shelma Maudy; Darmawan, Heru; Prasetya, Dwi Indra (JURNAL TEKNIK INDUSTRI, 2023)
PT. Chiyoda Industri Indonesia is a company involved in the automotive sector making car seat frames. One of the products is FR MNL Seat No.1 (Front) Handle/Handle Seat Track (YHA). Analysis using the quality control tool that is six sigma to determine the possibility of defects that often appear and find out the failure rate per million opportunities (DPMO). As an evaluation material for PT. Chiyoda Industri Indonesia in responding to demands from QC gate regarding defective products that are still found and potentially sent to customers. Analyzing defective samples in November 2022 - December 2022. The six sigma method consists of 5 stages. The stages are DMAIC which can be described as define, measure, analyze, improve and control. It was found that the sigma value is 3.2887 which is reaching the average level of the manufacturing industry in Indonesia and the number of DPMO is 41413.1299. Cause and effect diagram analysis of the most critical types of defects include pitch hole grooves with 50.1%, bending dimensions with 31.6%, pressing dimensions with 12.6%, swaging assy missing with 3.1%, and dents with 2.6%. From the analysis of the cause and effect diagram, it can be seen that the material factor is the focal point of the cause of defects until the material flows. And from the 5W+1H analysis, it is concluded that every process needs kaizen. In the FMEA analysis, the biggest problem is the grooving process which is the cause of the material not meeting the criteria of the process results on the previous machine, namely swaging large holes, long side bending, and top press with RPN 216.